Novel Writer’s Voice in Critical Annotated Bibliography - Harti, Laily Maulida Septiana Harti; Leliana, Ayunita; Adelia, Silvy Chintia Adelia (Universitas PGRI Adi Buana Surabaya, 2022)
Undergraduate students are required to think critically and put it into their writings and research. However, it is challenging for the students to do so, since they might encounter plagiarism issues, as they try to make use of their own voice. This study, carrying out a research and development design with a research subject of 77 students who programmed the Reading for Research course, aimed to produce educational products in the form of learning materials that can help them during their critical annotated bibliography composition. Data were collected in three stages using interview guidelines and inquiry journals in the preliminary research stage, observation sheet of validation form in the model development stage, and observation sheet in the form of field notes in the model trial stage. In the preliminary field testing of the use of the tutorials in the learning materials for Reading for Research class, it is found that writing Critical Annotated Bibliography while still including their voices as writers became easier for students. This is because the instructions used in the teaching materials that the writing team compiled are very explicit, so students can easily follow and execute the instructions in writing.